Tris(trimethylsilyl)phosphate: A film-forming additive for high voltage cathode material in lithium-ion batteries - Yan, Guochun; Li, Xinhai; Wang, Zhixing; Guo, Huajun; Wang, Chao (Journal of power sources, 2014)
Tris(trimethylsilyl)phosphate (TMSP) is investigated as a novel film-forming additive for LiNi sub(0.5)Co sub(0.2)-Mn sub(0.3)O sub(2) cycling at high cut-off potential in LiPF sub(6)-based electrolyte. Linear sweep voltammetry (LSV) results reveal that TMSP oxidizes prior to the decomposition of carbonate solvents in electrolyte. When TMSP is incorporated into the electrolyte, the electrochemical performance of LiNi sub(0.5)Co sub(0.2)Mn sub(0.3)O sub(2) is enhanced significantly. The initial discharge capacity of LiNi sub(0.5)Co sub(0.3)Mn sub(0.3)O sub(2) cathode material cycling in the electrolyte with 1 % TMSP is increased from 173.4 to 191.0 mAh g super(-1) compared with that without TMSP between 3.0 and 4.5 V (vs. Li/Li super(+)) at 0.1 C(1 C = 170 mA g super(-1)). In addition, it exhibits a capacity-retention of 90.9% at 1 C after 100 cycles, while that without TMSP is 77.0%. TEM, XPS, and EIS analyses confirm that the film derived from TMSP protects LiNi sub(0.5)Co sub(0.2)Mn sub(0.3)O sub(2) material from eroding by HF effectively, and reduces the interface impedance.